ECONOMIC ASSESSMENT OF THE WATER RESOURCE IN THE TUNSHI GRANDE COMMU-NITY, LICTO PARISH, PERIOD 2019 - Yerbabuena Tenelema, Jessica Karina; Aucancela Guamán, Margarita Alejandra (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019DO - 10.36779/mktdescubre/v#.#, 2020)
The present investigation deals with the environmental economic valuation of environmental services hydrological, the tributaries of the river basin of the community tunshi taguan Grande, establishing as the only source of water for domestic consumption in the community, but the abuse of the land used for agricultural practices, cause conflicts between producers and the community by the evident pollution, degradation and decline in the water potential. The problem is that users in the community are not paying for resource conservation, it is necessary to estimate of the valuation as it addressed this issue very soon you won’t have a sufficient amount of water to cover the needs of the population. We used the contingent valuation method (CVM) In order to get to know the willingness to pay (WTP) by the inhabitants of the community. Applied surveys to gather the data that were used to test a model logarithmic. The variables that were accepted in accordance with the model were household members, economic activity and the quality of water. The willingness to pay for conservation of water resources is $4.73 per month.